Changes in the avifauna of a relict forest in the Peri-Urban area of Bogota throughout fourteen years (2017)
The native vegetation of the Sabana de Bogota’s flat area has been replaced by agricultural lands, pastures and urbanizations over the years. The last relict of this native vegetation is a small forest (ca 10 ha) at Hacienda Las Mercedes, in the northern border of Bogota. The forest’s small size and isolation from other areas of natural vegetation have resulted in the loss of many species. The problem was exacerbated by uncontrolled growth of invasive vegetation (vines and wild blackberry). However, in recent years restorative action including control of these vegetation has been undertaken and the forest is now immerse in a natural reserve where more restorative actions are being planned. Using point count stations the authors recorded all the birds seen and heard in 2001-2002 and in 2014 in order to evaluate the changes in the bird community and estimate the effects of the restorative actions. We recorded 27 forest species in the first census and 30 in the second. The relative abundance of at least 1/3 of the species also increased indicating a positive result in the forest restoration. The results highlight the capacity of degraded ecosystems to recover and the importance of continuing the restorative actions in the reserve area